Al-Qur’an dan Ketoprak Pati: Kajian Living Qur’an Dalam Pertunjukan Budaya Lokal - Ahmad Nur Fuad; Fauzan Adim (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study aims to utilize the manifestation of Qur'anic values ​​in the Ketoprak Wahyu Budoyo performance in Pati Regency, as well as the role of comedic characters as a medium for transmitting moral and religious messages. The approach used in this study is Living Qur'an with a qualitative descriptive method through observation, interviews, and visual documentation. The results of the study indicate that Qur'anic values ​​such as trustworthiness, sacrifice, honesty, brotherhood, tolerance, and patience are committed through the storyline, character traits, symbols, and local cultural dialogue. Comedic characters play an important role in conveying moral messages through humor, songs, and communicative song lyrics. The novelty of this study lies in the analysis of the integration of Qur'anic values ​​through traditional arts using the Living Qur'an perspective, which is rarely studied in depth. This finding confirms that ketoprak art does not only function as a means of entertainment, but also becomes a space for cultural interpretation in bringing Qur'anic values ​​to life contextually.